Associations of living arrangements with symptoms and functioning in schizophrenia - Ang, Mei San (2022)
Background: Living arrangements and accommodation are closely related, but no study had concurrently investigated their associations with outcomes in schizophrenia. This study seeks to describe and compare sociodemographic, clinical and functioning profiles of people with schizophrenia in different living arrangements and accommodation, and to examine the associations of living arrangements and accommodation with symptomatic remission and functioning. Methods: Community dwelling outpatients with schizophrenia (n = 276) were inquired on living arrangements, accommodation, socio-demographics and assessed on the Positive and Negative Syndrome Scale (PANSS) and the Social and Occupational Functioning Scale (SOFAS). Socio-demographics, symptoms and functioning of outpatients in different living arrangements and accommodation were compared. Symptomatic remission was investigated using logistic regression with living arrangements, socio-demographics and clinical variables as independent variables. Functioning was investigated using multiple regression with the same set of independent variables and the addition of PANSS factors. The same analyses were conducted with accommodation as independent variable. Results: 185 (67.03%) participants lived with family and 195 (70.65%) participants lived in owned accommodation. People living with their spouses had significantly higher SOFAS, lower PANSS Total and PANSS Positive than people living with family, independently, or in rehabilitation centres. They also had lower PANSS Negative than people living with family and a higher likelihood to have achieved symptomatic remission. Types of accommodation was not associated with symptoms, symptomatic remission, and functioning. Conclusion: Living arrangements, but not types of accommodation, were associated with symptoms and functioning in schizophrenia. Family education and support is important to help maintain a conducive environment for people with schizophrenia. People living independently may need more support.